2015
DOI: 10.1080/00223131.2015.1034215
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen generation by water radiolysis with immersion of oxidation products of Zircaloy-4

Abstract: In order to predict the hydrogen gas generation from seawater or water in which debris would be included by the severe accident of nuclear power plant, we investigated the effect of ZrO 2 and the oxidation products of Zircaloy-4 on hydrogen gas generation by radiolysis of water since the radiolytic generation could be affected by materials immersed in water. Powders of well-characterized oxides and oxidation products were immersed in either seawater or distilled water, and irradiated by gamma ray from a Co-60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…In our previous study which used two commercial zirconium oxides indicated that the G(H 2 ) of yttria-stabilized tetragonal zirconia (t-ZrO 2 ) was larger than monoclinic zirconia (m-ZrO 2 ). The G(H 2 ), median particle diameter, and specific surface area of m-ZrO 2 were 2.1E -08 mol/J, 3 μm, and 19.6 m 2 /g and these of t-ZrO 2 were 4.2E -08 mol/J, 3 μm, and 63.2 m 2 /g (Matsumoto et al, 2015). However, in the experiments with water containing two different oxidation products of zry-4, the G(H 2 ) of the oxidation product T never exceeded the oxidation product M. We have calculated and compared the G(H 2 )/S of the oxidation products and two commercial zirconium oxides.…”
Section: Difference In H 2 Generation Between the Oxidation Products And Two Commercial Zirconium Oxidesmentioning
confidence: 95%
See 1 more Smart Citation
“…In our previous study which used two commercial zirconium oxides indicated that the G(H 2 ) of yttria-stabilized tetragonal zirconia (t-ZrO 2 ) was larger than monoclinic zirconia (m-ZrO 2 ). The G(H 2 ), median particle diameter, and specific surface area of m-ZrO 2 were 2.1E -08 mol/J, 3 μm, and 19.6 m 2 /g and these of t-ZrO 2 were 4.2E -08 mol/J, 3 μm, and 63.2 m 2 /g (Matsumoto et al, 2015). However, in the experiments with water containing two different oxidation products of zry-4, the G(H 2 ) of the oxidation product T never exceeded the oxidation product M. We have calculated and compared the G(H 2 )/S of the oxidation products and two commercial zirconium oxides.…”
Section: Difference In H 2 Generation Between the Oxidation Products And Two Commercial Zirconium Oxidesmentioning
confidence: 95%
“…We have oxidized the zry-4 under various conditions and crushed them to investigate the effects of the oxidation products on the H 2 generation by water radiolysis. The enhancement of H 2 generation seemed to be dependent on either the specific surface area or the particle size of the oxidation product, but it was not certain which is the predominant factor (Matsumoto et al, 2015). The characterization of the aerosol source term emitted during the laser cutting of fuel debris assumes that the particle mass size distributions corresponding to particle aerodynamic diameters between 0.01 and 10 µm (Porcheron et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The formation mechanisms of these phases were complicated and would require extra information from the accident product analysis. On the other hand, characterization of the oxidation products of Zircaloy is also relevant in considering the hydrogen safety in fuel debris storage . In some cases, ZrN, Zr oxynitrides, and ZrO 2 coexisted in a fine microstructure for which nanoscale analyses should be necessary, for those circumstances, transmission electron microscopy (TEM) and electron energy loss spectroscopy (EELS) are useful methods.…”
Section: Introductionmentioning
confidence: 99%